Switching Among Worlds: How Online Friends Encourage Code-Switching in Communication - Rainata Gracia; Syamdianita; Aridah; Maria Teodora Ping; Iwan Setiawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates code-switching in digital communication among bilinguals, focusing on informal conversations on WhatsApp and Discord. It aims to examine the types of Code-Switching that occur and the underlying motivations behind them. The study employs a qualitative case study approach, the research involved chat data analysis and semi-structured interviews with a 21-year-old Indonesian and an 18-year-old Malaysian, both of whom are online friends. Data were collected over a three months period (January-March 2025). Guided by Poplack’s typology, the analysis identified three types of code switching: intra-sentential, inter-sentential, and tag-switching with intra-sentential switching being the most frequent (76% of all instances). Participants reported that their language choices were influenced by social dynamics, emotional state and the context of the conversation. Reasons for code-switching were for expressive clarity, social connection and cultural identity reinforcement. While limited by its small sample and short timeframe, this study highlights how digital platforms facilitate linguistic flexibility and position Code-Switching as a strategic tool for interpersonal communication. The findings contribute to the fields of sociolinguistic and digital communication by providing insight into how online communication shapes multilingual practices in contemporary context.